Qawa’id wa Tarjamah Method and Card Sort Strategy in Shorof Learning in Madinah Modern Boarding School - Muhammad Afif Amrulloh; Reni Puspita (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
The purpose of this study was to find out the application of the qowa'id wa tarjamah method with card sort strategy in improving the shorof ability of the 9th grade student’s at Madinah Modern Boarding School . This research is a Classroom Action Research study. It is the research which oriented to solving the problems that occurred in the classroom by improving the learning process in accordance with the expected goals. Research analysis was conducted inductively. The research used qualitative research, the data in the form of verbal and analysed without using statistical techniques. This classroom action research consists of two cycles through four stages of the process as follows: 1) the planning stage, 2) the implementation stage, 3) the observation stage, and 3) the reflection stage. The application of the qowa’id wa tarjamah method with card sort strategy can improve shorof ability towards 9th grade student’s of the Madinah Modern Boarding School . Student’s are able to understand the material well and make sentences and are enthusiastic in participating in class teaching and learning activities. This can be proven by improving the shorof ability of the student’s in each cycle.